Korean Wave as a Tool of Public Diplomacy: The Impact of South Korean Cultural Globalization in Indonesia from 2018 to 2023 - Asri Suratmi (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The Korean wave refers to the global popularity of South Korean culture. It is a powerful public diplomacy tool to improve a country's image and influence abroad. The Korean wave has been instrumental in shaping South Korea's international reputation. The rise of K-pop and Korean dramas has boosted the country's economy. In addition, the experience of living abroad can be transformative because it encourages students to step out of their comfort zone and learn to adapt to new environments. This personal growth and self-discovery contribute to their overall development and equip them with valuable skills that are highly sought after in today's globalized world. Studying the Korean Wave as a cultural phenomenon is important in today's globalized world. From K-pop music and K-dramas to fashion and beauty trends, the Korean Wave has attracted the attention and admiration of people from different countries and backgrounds. By understanding the Korean Wave, students gain insight into the power of popular culture in shaping global trends and influencing societal norms. In addition, studying the Korean Wave can give students a unique perspective on cultural globalization and the connectedness of various Societies.